SAT0302 Active Systemic Lupus Erythematosus Associates with Carotid Intima-Media Thickness Progression. (15th July 2016) - Berti, A.; Baragetti, A.; Magnoni, M.; Garlaschelli, K.; Grigore, L.; Berteotti, M.; Scotti, I.; Bozzolo, E.; Ramirez, G.A.; Manfredi, A.A.; Ammirati, E.; Catapano, A.L.; et al.
Abstract : Background: A relationship between systemic inflammation and increased cardiovascular risk is often postulated. Simple and affordable clinical predictors of increased cardiovascular risk in patients with autoimmune disease, however, are not yet available in the clinical practice. Objectives: To address the role of clinical, serological markers of disease activity, and of classical cardiovascular risk factors (CVRF) in predicting the carotid intima-media thickness (c-IMT) progression at 5 years (Δc-IMT) in patients with the prototypic autoimmune disease systemic lupus erythematosus (SLE). Methods: Clinical and biochemical data including SLEDAI were collected at baseline and at five years of follow up from 50 patients with SLE and 50 age- and gender-matched healthy controls. C-IMT was also measured at baseline and at 5 years to evaluate progression. Results: A higher SLEDAI score at baseline correlated with a faster Δc-IMT (0.007 (0.006) mm/year vs 0.003 (0.001) mm/year when compared to controls, P=0.026), irrespectively of the presence of CVRF and of the serological profile. Patients with higher SLEDAI score at baseline also experienced disease flares more frequently (p=0.037) than those with milder disease at baseline. Patients with a higher disease activity during follow up had also a faster Δc-IMT when compared to those with a persistently low disease activity (0.008 (0.004) mm/year vs -0.006 (0.004) mm/year, P=0.021). Elevated LDL-C levels were the only CVRF associated with disease flare-up; this might a consequence of the aggressive immunosuppressant therapy in those patients. Conclusions: Patient with SLE show an increased cardiovascular risk as estimated by the c-IMT. Disease activity and in particular disease flares accelerate the progression of the vascular damage. Disclosure of Interest: None declared